Economic system and the size distribution of income and wealth - Pryor, Frederic L. (Bloomington, International Development Research Center, Indiana University, 1971)
In analyzing and comparing the size distribution of income in nations with different economic systems, we must examine closely not only the determinants of the size distribution of labour income, but also of the size distribution of wealth.
Includes bibliographical references.
osc 21/09/2021
Loans
Keywords: Income distribution; Wealth